The effect of a web-based lifestyle intervention on nutritional status and physical activity on prevention of COVID-19: a randomized controlled trial in women's empowerment - Pourfarzi, Farhad; Kamran, Aziz; Zare, Maryam; Mohammadshahi, Jafar (Frontiers in Nutrition, 2024)
Background Healthy dietary intake and physical activity affect the immune systems. The present study aimed to investigate the effects of a web-based lifestyle intervention on nutritional status, physical activity, and prevention of COVID-19. Methods Three hundred-three women (30–60 years old), who did not have COVID-19 in the City of Ardabil, participated in this study. Participants were randomized into an intervention (n = 152) or control group (n = 151). The intervention group received eight online educational sessions focusing on a healthy diet and physical activity via the website. There was no educational session for the control group during the intervention, but they were placed on the waiting list to receive the intervention and given access to the website and educational content after the follow-up. Outcomes were nutritional status, physical activity, immunoglobulin G (IgG), and immunoglobulin M (Ig M) antibody titers against the virus. They were evaluated at the baseline, after 4 and 12 weeks. Results Significant improvements in weight (P < 0.001), BMI (P < 0.001), total energy (P = 0.006), carbohydrate (P = 0.001), protein (P = 0.001), and fat (P < 0.001) were found for the intervention group compared to the control group during the study. MET-min/week for moderate physical activity increased during the time for the intervention and control groups (P < 0.001 and P = 0.007, respectively). MET-min/week for walking activity rose in the post-intervention and follow-up compared to that in the baseline in the groups (P < 0.001 for both groups). Total physical activity was increased during the study (P < 0.001) for both groups. The mean of serum IgG and IgM titers against the virus were increased during the study in both groups in time effect (P < 0.001). There was a significant time x group interaction for carbohydrate and fat intakes (P = 0.005 and P = 0.004, respectively). Conclusion The web-based lifestyle intervention may improve nutritional status and physical activity, and have the potential to reduce the risk of contracting a COVID-19 infection.